Moral responsibility - Cowley, Christopher, 1967-; Cambridge eBooks (Durham : Acumen Publishing, 2014)
How and to what degree are we responsible for our characters, our lives, our misfortunes, our relationships and our children? This question is at the heart of Moral Responsibility. The book explores accusations and denials of moral responsibility for particular acts, responsibility for character, and the role of luck and fate in ethics. Moral responsibility as the grounds for a retributivist theory of punishment is examined, alongside discussions of forgiveness, parental responsibility, and responsibility before God. The book also discusses collective responsibility, bringing in notions of complicity and membership, and drawing on the seminal contemporary discussion of collective agency and responsibility: the Nuremberg trials.
I. Retrospective responsibility. Defining retrospective responsibility -- Responsibility for mistakes -- Apology and forgiveness -- Punishment -- Moral luck -- II. Prospective responsibility. Role-responsibility -- Responsibility for strangers -- Learning to love.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Responsibility; Free will and determinism; Electronic books